2016
DOI: 10.15171/jlms.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Irradiation Low Intensity on Reparative Osteogenesis and Angiogenesis Under Transosseous Osteosynthesis

Abstract: IntroductionThe use of non-medicinal facilities of correcting the processes of reparative regeneration for various pathological conditions is one of the most urgent problems in modern medicine. Laser therapy of different types is widely used in clinical practice including traumatology and orthopaedics for treating the locomotorium injuries and diseases, and it is aimed to provide the anesthetizing, anti-edematous, anti-inflammatory and trophic-stimulating effects. [1][2][3][4] Besides, it ensures the decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
4
Order By: Relevance
“…In recent years, many studies have shown that LLLT promotes the differentiation of bone marrow mesenchymal stem cells and promotes endothelial cells angiogenesis in vitro [ 16 , 35 , 36 ]. Meanwhile in vivo studies have confirmed that LLLT promotes angiogenesis, osteogenic differentiation of stem cells, and fracture healing [ 37 , 38 ]. However, whether LLLT is coupled with blood vessel formation, and bone formation is related to bone repair and regeneration, is not very clear.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have shown that LLLT promotes the differentiation of bone marrow mesenchymal stem cells and promotes endothelial cells angiogenesis in vitro [ 16 , 35 , 36 ]. Meanwhile in vivo studies have confirmed that LLLT promotes angiogenesis, osteogenic differentiation of stem cells, and fracture healing [ 37 , 38 ]. However, whether LLLT is coupled with blood vessel formation, and bone formation is related to bone repair and regeneration, is not very clear.…”
Section: Discussionmentioning
confidence: 99%
“…Низькоінтенсивна лазеротерапіязастосування в медичних цілях лазерного випромінювання низької інтенсивності для якого характерні фіксована довжина хвилі (монохроматичність), однакова фаза випромінювання фотонів (когерентність), висока направленість та фіксована орієнтація векторів електромагнітного поля в просторі (поляризація). У фізіотерапії використовують переважно червоне та інфрачервоне випромінювання [29,30].…”
Section: низькоінтенсивна лазеротерапіяunclassified
“…В основі репаративного ефекту НЛТ лежить активація проліферації низки клітин в зоні тканинного дефектумакрофагів, лімфоцитів, кератиноцитів, фібробластів, ендотеліальних клітинвнаслідок посилення продукції факторів росту судинного ендотелію (VEGF), фібробластів (FGF), тромбоцитарного фактору росту (PDGF) [29,31,32].…”
Section: низькоінтенсивна лазеротерапіяunclassified
“…Atualmente, existem métodos para aliviar o processo inflamatório, proporcionando melhoria na nutrição celular e favorecendo o reparo tecidual danificado (Melo et al, 2011). O uso de terapias alternativas não medicinais para corrigir os processos de regeneração reparadora em várias condições patológicas é um dos problemas mais urgentes da Medicina Moderna (Iryanov, 2016).…”
Section: Introductionunclassified
“…A terapia com laser de diferentes tipos é amplamente utilizada na prática clínica e visa proporcionar os efeitos anestésicos, anti-edematosos, antiinflamatórios e tróficos-estimulantes. Além do mais, é um tratamento confortável, não-invasivo, asséptico, indolor, inofensivo e controlável (Iryanov, 2016), sendo bem tolerada por tecidos biológicos e sem associação com efeitos Deletérios (Fiório et al, 2011).…”
Section: Introductionunclassified